Book Reviews (Historia, 2021)
1. A. Davey, The British Pro-Boers 1877-1902 2. M.M. Boshoff (red.) French Publications on South Africa3. B. Schoeman, My Lewe A die Politiek 4. P.M. Hayes, The Twentieth Century, 1880-1939 5. J.F. Schwar & R. W. Jardine (tr. & ed.), The Letters of Gustav Steinbart 6. P.J. de Vos, Die Sosiale Denke van die Antieke Nabye Ooste en Die Sosiale Denke van die ou Grieke en Romeine 7. P. Tobias (ed.), The Bushmen8. J.R. Bruijn, Het gehg der zeelieden9. H. Toerien & G. Duby , Ons Kuns 10. P.B. van der Watt; Die Nederduitse Gereformeerde Kerk11. A.P. Cartwright & N. Cowan, The Old Transvaal, 1834-189912. G.B. Dickason, Cornish Immigrants to South Africa, 1820-1920 12. J.C. Moll (red.), F. W. Reitz - outobiografie 13. F.A. van Jaarsveld, Omsingelde Afrikanerdom 14. J. van der Byl (samesteller) Die Familie Roux en H.P. Kotze (samesteller) Geslagregister van TJ.Kotzeeen M.G. Louw 15. J.D. Fage, An Atlas of African History